MULTILINGUALISM AND ITS IMPACT ON CHARACTERS IN BRITISH COLONIAL PLAYS: A LINGUISTIC ANALYTICAL STUDY - Wildan Sawash Adnan (Scholars Digest Publishing, 2024)
This take a look at explores the function of multilingualism in British colonial plays and its impact on character improvement, electricity dynamics, and cultural identity. By that specialize in works from colonial and postcolonial intervals, which include Wole Soyinka's A Dance of the Forests, Athol Fugard's Sizwe Banzi is Dead, and Derek Walcott's Dream on Monkey Mountain, the research highlights how the interaction among colonizers' and indigenous languages shapes the characters' identities and relationships. Using a combination of discourse analysis and man or woman examine, the look at uncovers how language capabilities as each a device of colonial oppression and resistance. The analysis demonstrates that multilingualism in these performs reflects the complexities of colonial societies, wherein language serves as a symbol of both cultural erasure and renovation. The take a look at contributes to postcolonial literary studies by using presenting insights into how language, identity, and strength are intertwined in colonial and postcolonial drama, and indicates regions for in addition studies, which include the performative components of multilingualism and the role of translation in postcolonial theater.
Keywords: Multilingualism, British Colonial Plays, Language and Power, Cultural Identity, Postcolonial Drama